2018
DOI: 10.1097/paf.0000000000000381
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy Case of a Penetrating Wound to the Left Cerebral Hemisphere Caused by an Accidental Shooting With a Crossbow

Abstract: A crossbow is a bow that shoots an arrow when a gun-like trigger is pulled. Deaths caused by accidental crossbow shootings are extremely rare. Here we describe an autopsy case of a penetrating wound to the left cerebral hemisphere caused by an accidental shooting with a crossbow. A man in his early 60s who lived with his wife and had used crossbows for 20 years as his hobby was found one early morning in the shed of his house, collapsed and bleeding from the head and neck. He was taken to a hospital and died a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Previous reports have indicated that there is no difference in the pathological characteristics of injuries caused by suicide, accident, and homicide. 6) The overall survival rate was 80% (4/5 cases) according to the previous reports. 3,[5][6][7] Regarding the reason for death, it was considered to be caused by the site of injury rather than differences in the mechanism of injury (e.g., the main cause of death was brain injury in Kondo's report).…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Previous reports have indicated that there is no difference in the pathological characteristics of injuries caused by suicide, accident, and homicide. 6) The overall survival rate was 80% (4/5 cases) according to the previous reports. 3,[5][6][7] Regarding the reason for death, it was considered to be caused by the site of injury rather than differences in the mechanism of injury (e.g., the main cause of death was brain injury in Kondo's report).…”
Section: Discussionmentioning
confidence: 67%
“… 3 , 5 - 7 ) Regarding the reason for death, it was considered to be caused by the site of injury rather than differences in the mechanism of injury (e.g., the main cause of death was brain injury in Kondo's report). 6 ) Among them, a case of removal of a crossbow bolt under fluoroscopy with the assistance of an endovascular approach has not been reported. In 75% of these cases, the blood vessels were in contact with a crossbow bolt.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations